48.2k views
4 votes
Find (gOf)(3)
f(x)=3x-2
g(x)=x^2

User Greg Viv
by
8.6k points

2 Answers

6 votes
f(x)=3x-2
g(x)=x^2
(g o f)(3)=?

(g o f)(3)=g(f(3))
x=3→f(3)=3(3)-2
f(3)=9-2
f(3)=7

(g o f)(3)=g(f(3))=g(7)
x=7→g(7)=7^2
g(7)=49

Answer: (g o f)(3)=49
User Michal Chudy
by
8.6k points
7 votes
For this case, the first thing we must do is the composition of functions.
We have:
f (x) = 3x-2
g (x) = x ^ 2
(gOf) (x) = (3x-2) ^ 2
We now evaluate the function:
(gOf) (3) = (3 * (3) -2) ^ 2
(gOf) (3) = (9-2) ^ 2
(gOf) (3) = (7) ^ 2
(gOf) (3) = 49
Answer:
(gOf) (3) = 49
User Idan Ayzen
by
8.4k points